2015
DOI: 10.5935/1678-9741.20150046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two technics of extracorporeal circulation (Conventional and Mini ECC), in the trans and post-operative periods of cardiac surgery

Abstract: ObjectiveThis study aimed to compare the effects of two different perfusion techniques: conventional cardiopulmonary bypass and miniature cardiopulmonary bypass in patients undergoing cardiac surgery at the University Hospital of Santa Maria - RS.MethodsWe perform a retrospective, cross-sectional study, based on data collected from the patients operated between 2010 and 2013. We analyzed the records of 242 patients divided into two groups: Group I: 149 patients undergoing cardiopulmonary bypass and Group II - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…In a comparable cohort analyzed by Perthel et al patients on MCPB support showed higher hemoglobin levels and reduced postoperative hemorrhage . These findings were confirmed in 2015 by Pereira et al who reported reduced erythrocyte transfusion rates and increased postoperative hematocrit and hemoglobin levels after CABG with MCPB systems . In this study, the difference of hemoglobin between conventional and minimized bypass circuits was only about 1 g/dL.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In a comparable cohort analyzed by Perthel et al patients on MCPB support showed higher hemoglobin levels and reduced postoperative hemorrhage . These findings were confirmed in 2015 by Pereira et al who reported reduced erythrocyte transfusion rates and increased postoperative hematocrit and hemoglobin levels after CABG with MCPB systems . In this study, the difference of hemoglobin between conventional and minimized bypass circuits was only about 1 g/dL.…”
Section: Discussionsupporting
confidence: 80%
“…Studies comparing conventional and minimized bypass circuits for CABG focus on the read out such as mortality, stroke, need for perioperative blood component transfusion, myocardial damage, atrial fibrillation, renal failure, and inflammatory response triggered by the extracorporeal circuit . To our knowledge, this is the first study that analyses differences between conventional and minimized cardiopulmonary bypass systems by means of perfusion parameters and their course during extracorporeal support.…”
Section: Introductionmentioning
confidence: 99%
“…12 With regard to the issue of blood transfusions, our results are consistent with those of other authors, who report lower rates of blood transfusions in patients operated with the use of MiECC systems. 2,13,14 The issue of blood transfusion after cardiac surgery has been extensively discussed in literature. Low haemoglobin levels have been shown to be associated with myocardial injury, increased inotrope requirements, neurologic dysfunction and stroke, renal dysfunction and postoperative dialysis, prolonged ventilation, and increased perioperative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In the conditions of modern anesthetic technology and perfusion, a considerable amount of information has accumulated on various methods of preventing SIR, which are effective to a greater or lesser extent. We offer an overview of the most commonly used methods for the prevention of SIR (see Table 2) [43,[78][79][80][81][82][83][84][85][86][87][88][89].…”
Section: You Need To Know the Enemy By Sight Or How Not To Pass By De...mentioning
confidence: 99%